2019
DOI: 10.30827/publicaciones.v49i4.11730
|View full text |Cite
|
Sign up to set email alerts
|

Integración del aprendizaje-servicio en el modelo de educación deportiva como facilitador de la transición a la educación secundaria

Abstract: El presente trabajo describe la propuesta e impacto de un programa basado en la aplicación integrada del Aprendizaje-Servicio (ApS) en el Modelo de Educación Deportiva (MED), en la creación de facilitadores para la transición de Educación Primaria (EP) a Educación Secundaria (ES). La muestra estuvo compuesta por seis docentes, 142 estudiantes de sexto curso de EP y 64 de ES. Se creó una red deportiva de centros según los preceptos del MED y se utilizó la red social educativa Edmodo para la coordinación de los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 21 publications
1
7
0
14
Order By: Relevance
“…On the other hand, moving now to the quantitative investigations or the quantitative part of those using mixed methods, a very recurrent research instrument was questionnaires [ 28 , 30 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The validated questionnaires used were the Entrepeneurship Competency Scale [ 51 ], the Subjective Happiness Scale [ 28 ], and the Multidimensional Attitudes Scale Toward Persons With Disabilities questionnaire [ 29 ], among others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, moving now to the quantitative investigations or the quantitative part of those using mixed methods, a very recurrent research instrument was questionnaires [ 28 , 30 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The validated questionnaires used were the Entrepeneurship Competency Scale [ 51 ], the Subjective Happiness Scale [ 28 ], and the Multidimensional Attitudes Scale Toward Persons With Disabilities questionnaire [ 29 ], among others.…”
Section: Resultsmentioning
confidence: 99%
“…First, regarding the research limitations, we have found the following: Research design. Some papers express that their investigations were short, thus limiting their understanding of the long-term effects of SL [ 26 , 33 , 34 , 46 ]. Sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incluso remarcó que "mientras que antes los alumnos no colaboraban con él para intentar ayudarlo en sus dificultades, su grupo ha estado más pendiente de él". Los resultados alcanzados se sitúan en la línea de trabajos anteriores, que habían mostrado el potencial de modelo para integrar en el aula a estudiantes que suelen estar discriminados (Gutiérrez et al, 2019;Hastie, 1998;MacPhail et al, 2004;Puente-Maxera et al, 2018).…”
Section: Discussionunclassified
“…The increased scientific evidence and teaching literature on Sport Education in Spain and the initial expansion of the method stemming from its inclusion in teacher training programs at the regional university in 2008, led policy makers in the autonomous region of Castilla-La Mancha (Spain) to promote Sport Education model across the region. Three specific measures have helped boost the profile of Sport Education in Castilla-La Mancha: (1) providing for its use in teaching recommendations within the primary education curriculum (Decree 54, 2014), underlining its potential for the development of values; (2) integrating it in the Healthy School Projects (HSP) initiative, which proposes its progressive incorporation into schools and teacher development programs; and (3) promoting Sport Education school networks, with aims such as the transition to secondary education (Gutiérrez, Segovia, García-López, & Fernández-Bustos, 2019) or the promotion of new sports.…”
Section: Introductionmentioning
confidence: 99%